The Protective Effects of Exogenous Melatonin on Nicotine-induced Changes in Mouse Ovarian Follicles - F Mohammadghasemi; S Khajeh Jahromi; H Hajizadeh; MA Homafar; N Saadat (JRI, 2012)
Background: Nicotine exposure causes impaired fertility and ovarian dysfunction. The aim of this study was to investigate the possible protective role of melatonin, which is known as an antioxidant agent on altered ovarian functions upon nicotine exposure. Methods: A total of 32 female adult NMRI mice were divided randomly into four groups (n=8). The control group received vehicle, while group 2 received nicotine (40 μg/kg) for 15 days and group 3 melatonin (10 mg/kg) for 5 days. Group 4 received both nicotine (40μg/kg) and melatonin (10 mg/kg) for the same periods. All animals were treated intraperitoneally. After autopsy on the 16th day, histopathological and morphometrical examinations were performed and serum estradiol concentrations were measured. The data were analyzed using ANOVA and Tukey post hoc test. A value of p<0.05 was considered significant. Results: Nicotine significantly reduced the number of pre-antral and antral follicles, as well as estradiol concentration compared to the control group (p<0.05). However, the decrease in the number of primordial follicles was not significant in the nicotine treated group. A significant increase in the atretic follicles were observed in group 2 compared to the control group (p<0.05). Moreover, melatonin caused a marked normalization in the number of ovarian follicles and estradiol levels in group 4 compared to group 2. Conclusion: The results from this study suggest that melatonin may have a protective effect against nicotine-induced ovarian changes on the number of different stages of follicle growth.
Keywords: Nicotine, Melatonin, Mouse, Ovary, Protection, Ovarian follicles